Exploring the Impact of Social Media Marketing on Malaysia’s Food Truck Industry - Mohd Jamil, Jastini; Mohd Shaharanee, Izwan Nizal; Abdul Aziz, Aifaa Zaffan Bagauddin (Management Research Journal, 2024)
This study examines the effectiveness of social media as a marketing tool in Malaysia’s rapidly growing food truck industry. Given the widespread adoption of digital platforms, understanding the dynamics that enhance social media’s effectiveness in marketing has become crucial. This research specifically investigates the relationship between the perceived usefulness of social media and key factors such as informativeness, credibility, hedonic value, and co-creation value. Data were collected from 201 Malaysian social media users interacting with food truck businesses using a quantitative survey method. Analytical methods included descriptive statistics, Pearson’s correlation, multiple regression analysis, and ANOVA tests to assess the impact of demographic variables on perceived usefulness. The findings highlight that informativeness and credibility are critical drivers of perceived usefulness in social media marketing. The results support the Technology Acceptance Model (TAM), suggesting that effective social media marketing strategies should focus on enhancing the quality and reliability of content to foster consumer engagement. This study offers practical insights for food truck owners on optimizing social media usage to attract and retain customers effectively. It also identifies future research directions, emphasizing the need for a broader demographic approach and exploration of emerging digital marketing trends. This research contributes to academic literature and practical marketing strategies, guiding food truck businesses to leverage digital platforms for enhanced market engagement and growth.